Pelatihan Kesehatan dan Keselamatan Kerja Pada Kelompok Nelayan di Kawasan Pesisir - Naura Salsabilla Hrp; M Farouq Al azid Mrp; Zanzabila Aulya Rokan; Abdurrozzaq Hasibuan (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Fisherman is one of the jobs that entails dangers also risk of accidents as well as occupational diseases gien that fishing activities take place either at sea or along the coast. Fishermen require personal protective equipment to minimize the risk of accidents also occupational diseases. Most fishermen in Indonesia are traditional divers, meaning they have been diving passed down through generations without being provided with sufficient knowledge of diving safety also health knowledge (safety diving). The aim of this training is to provide fishermen with an understanding of the importance of occupational safety also health for fishermen.